Phylogenetic relationships in Nothofagus: a preliminary approach based on morphological characters - Caviglia, Nicolás (2019)
Fil: Passalia, Mauro Gabriel. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigaciones en Biodiversidad y Medioambiente. Río Negro. Argentina